INTERVENSI VAP BUNDLE PADA NEONATUS DENGAN RESPIRATORY DISTRESS SYNDROME YANG TERPASANG VENTILATOR MEKANIK: CASE STUDY - Sasadhara, Avinnia; Indarwati, Ferika; Anisah, Layli (NHM PRESS, 2024)
Background: VAP occurs due to nosocomial infection in patients who have been intubated with a mechanical ventilator using an ETT with a duration of use ≥ 48 hours. This nosocomial pneumonia can be prevented by implementing VAP bundle interventions aimed at reducing the risk of VAP in patients. Purpose: To assess the effect of VAP bundle interventions in a neonatal patient with respiratory distress syndrome who is intubated with a mechanical ventilator. Methods: The method used in this research is a case study implementing the 5 elements of VAP bundle intervention carried out for 5 days in a neonatal patient intubated with a mechanical ventilator in the PICU-NICU room of the Regional Public Hospital of Temanggung Regency. Results: The results of this case study showed that after implementing the VAP bundle interventions for 5 days in a row, most of the clinical criteria of VAP were not found in the neonatal patient, such as HR, RR, SpO2, and temperature were stable on average and secretion production during suction was white with liquid consistency. Conclusion: The implementation of VAP bundle interventions can prevent the occurrence of VAP in neonatal patient with respiratory distress syndrome who is intubated with a mechanical ventilator.